A priority sector - Gill, Sitara; Rana, Abdul Wajid (News International, 2022)
Pakistan is mainly an agricultural economy. According to the Economic Survey of Pakistan 2020-21, agriculture accounts for a share of 19.2 percent in GDP and constitutes a significant portion of exports at 60 percent. The agriculture sector is a major employer in the country with a bulk of 45 percent in the labour force and a source of livelihood for about 68 percent of the rural population.